Phytochemical analysis of habbatus sauda' / Azuin Mustafa, Hannis Fadzillah Mohsin and Ibtisam Abdul Wahab - Mustafa, Azuin; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Academy of Contemporary Islamic Studies (ACIS), 2016)
This study aimed to highlight the Islamic prophetic medicinal herb called Habbatus Sauda' or black cumin. It is botanically known as Nigella sativa (plant family: Ranunculaceae). Historically, this herb is used for the treatment of a cold symptom, skin condition like eczema, cough, bronchitis, against indigestion, promote lactation, headaches, toothaches and to treat diarrhea. The medicinal use of this herb includes anti-diabetes, immunopotentiating, immunomodulating, presenting the analgesic effect, anti-microbes, anti-inflammatory agent, and antioxidant. The focus of this study is to review the phytochemicals of Nigella sativa from the scientific journals. From the literature, the extracts were analyzed in order to detect various potential compounds. It was anticipated that major constituents such as the phenolics, alkaloids, steroids, terpenoids and cardiac glycosides could be acquired from this miracle herb. In the methodology, the fractionation of a Nigella extract was carried out via liquid chromatographic technique. Finally, an aromatic aldehyde was suggested, following a preliminary spectroscopic analysis